Alejo Carpentier, from Niggerism to the Marvellous Real-life (Anclajes, 2024)
The present article analyzes the roots of the famous formula, “the American Marvelous Real,” first published by Alejo Carpentier in 1948. The analysis suggests that the origins of this proposal can be traced to his first novel, ¡Écue-Yamba-Ó! (1927-1933). Its “Negrism” would later be revised and corrected in Carpentier´s second novel, which marked the beginning of what he called his “American Cycle.” The differences between the two texts are significant, and reveal the way in which Carpentier, in his second text, sought to construct not only a portrayal of the colonial past and its complex forms of subjugation, but also a representation of true Latin American “reality”.  This evolution, which we are here analyzing in the intellectual context of the 1930s, and from the perspective of the critique of ¡Écue-Yamba-Ó!  by Juan Marinello in particular, would be crucial in the elaboration of the Americanist proposal, which has been initiated with El reino de este mundo (1949).
Keywords: Alejo Carpentier; Negrism; Marvellous Real; Realism; New Novel